Relationship Of Stress Level And Motivation Of Making Final Task In Student At Faculty Of Medicine And Veterinary Medicine Universitas Nusa Cendana - Muhammad Helmi Alvin (Universitas Nusa Cendana, 2025)
Background : Stress is a common thing that found in students. Compared to the general population, medical students have higher stress levels. Especially when students are working on a thesis or final task. One instrument to measure stress levels is the DASS (Depression, Axiety, Stress Scale). High stress levels might be makes negative impact on individuals. One of the effects of stress is the level of motivation, in this case, the motivation of students in preparing their thesis. The instrument used to measure the level of motivation is the MSLQ (Motivated Strategies for Learning Questionnaire). Aim : Knowing the relationship between stress levels and the motivation to write a thesis for Medical Students, Faculty of Medicine and Veterinary Medicine, University of Nusa Cendana. Method : Observational analytic research with cross-sectional method. Determining the number of samples using the Lemeshow formula obtained 53 respondents using a purposive sampling technique from a total population of 60 respondents for the 2019 class. The analysis test for the two variables used the somers'd which is non-parametric test. Result : The results of the somers'd test analysis showed p value = 0.023 and r value = -0.332 The p value indicated that there was a significant relationship between stress levels and motivation. The r value indicates that the relationship between the two is negative at a moderate level. Conclusion : There is a significant relationship between the level of stress and the level of motivation of Medical students Nusa Cendana University. Keywords: Stress level; motivation level; thesis.